Phylogeny of Macrobrachium spp. (Decapoda, Pleocyemata) from Peru based on mitochondrial and nuclear data reveals a species complex comprising M. digueti (Bouvier, 1895) and M. transandicum Holthuis, 1950 - Eliana Zelada-Mázmela; Lorenzo E. Reyes-Flores; Luis De Stefano-Beltrán (ZooKeys)
Prawns of the genus Macrobrachium represent a highly diverse group of high commercial value worldwide. Eight Macrobrachium species have been reported from the Peruvian Pacific slope, but their phylogenetic relationships are still unknown. To investigate the systematics of Macrobrachium species from Peru, morphological identification and molecular data from nucleotide sequences of three genes were used: cytochrome c oxidase subunit I, 16S rRNA, and 28S rRNA. Based on morphological taxonomy, six species were successfully identified: M. americanum, M. digueti, M. gallus, M. inca, M. panamense, and M. transandicum. However, the phylogenetic inference results supported the species validity of only the first five species; all prawn individuals that were morphologically identified as M. transandicum were recovered within the M. digueti group, showing interspecific genetic distances near zero, suggesting that both species belong to the same species-level lineage, which may represent in the “olfersii species complex”. Our analyses also corroborated the genetic proximity of sibling species M. inca–M. americanum and M. gallus–M. panamense, and the monophyletic origin of Macrobrachium species from Peruvian populations. This study represents the first comprehensive phylogenetic analyses of Macrobrachium species from Peru, and contributes the first publicly available DNA sequences for M. inca and M. gallus, as well as the first sequences of M. americanum, M. panamense, M. digueti, and M. transandicum collected from Peruvian rivers.